Abandono afetivo nas relações de conjugalidade: responsabilidade civil e dano moral - Faria, Cristiane Gonzalez Basile de (2023)
The changes that occur in our family environments reflect not on the daily life of society, therefore, on legal relationships. These reflections refer to the legal system adversities and situations that, to accompany them, it becomes necessary a process of constant adaptation, often complex. Affection, the main axis of relationships, assumes a relevant role in these changes, as it interferes with family relationships as a result of these changes. This compensation is necessary because, when investing in a relationship, the person depends on feelings, time, expectations and a set of attitudes that corroborate the construction of the relationship, which, once found, requires a framework for the reconstruction of each other's lives. one. one, without the existence of a marital relationship